Age-appropriate services for people diagnosed with young onset dementia (YOD): a systematic review. (3rd August 2018) - Mayrhofer, Andrea; Mathie, Elspeth; McKeown, Jane; Bunn, Frances; Goodman, Claire
ABSTRACT: Background: Literature agrees that post-diagnostic services for people living with young onset dementia (YOD) need to be age-appropriate, but there is insufficient evidence of 'what works' to inform service design and delivery. Objective: To provide an evidence base of age-appropriate services and to review the perceived effectiveness of current interventions. Methods: We undertook a systematic review including all types of research relating to interventions for YOD. We searched PubMed, CINHAL Plus, SCOPUS, EBSCO Host EJS, Social Care Online and Google Scholar, hand-searched journals and carried out lateral searches (July–October 2016). Included papers were synthesised qualitatively. Primary studies were critically appraised. Results: Twenty articles (peer-reviewed [ n = 10], descriptive accounts [ n = 10]) discussing 195 participants (persons diagnosed with YOD [ n = 94], caregivers [ n = 91] and other [ n = 10]) were identified for inclusion. Services enabled people with YOD to remain living at home for longer. However, service continuity was compromised by short-term project-based commissioning and ad-hoc service delivery. Conclusion: The evidence on the experience of living with YOD is not matched by research and the innovation needed to mitigate the impact of YOD. The inclusion of people with YOD and their caregivers in service design is critical when planning support in order to delay institutional care